Cell‐Specific Transposable Element and Gene Expression Analysis Across Systemic Lupus Erythematosus Phenotypes - Zachary Cutts; Sarah Patterson; Lenka Maliskova; Kimberly E. Taylor; Chun Jimmie Ye; Maria Dall'Era; Jinoos Yazdany; Lindsey A. Criswell; Gabriela K. Fragiadakis; Charles Langelier; John A. Capra; Marina Sirota; et al. (ACR Open Rheumatology)
Objective There is an established yet unexplained link between interferon (IFN) and systemic lupus erythematosus (SLE). The expression of sequences derived from transposable elements (TEs) may contribute to SLE phenotypes, specifically production of type I IFNs and generation of autoantibodies. Methods We profiled cell‐sorted RNA‐sequencing data (CD4+ T cells, CD14+ monocytes, CD19+ B cells, and natural killer cells) from peripheral blood mononuclear cells of 120 patients with SLE and quantified TE expression identifying 27,135 TEs. We tested for differential TE expression across 10 SLE phenotypes, including autoantibody production and disease activity. Results We found 731 differentially expressed (DE) TEs across all SLE phenotypes that were mostly cell specific and phenotype specific. DE TEs were enriched for specific families and open reading frames of viral genes encoded in TE sequences. Increased expression of DE TEs was associated with genes involved in antiviral activity, such as LY6E, ISG15, and TRIM22, and pathways such as IFN signaling. Conclusion These findings suggest that expression of TEs contributes to activation of SLE‐related mechanisms in a cell‐specific manner, which can impact disease diagnostics and therapeutics.